Dynamic behavior and modeling of prismatic lithium‐ion battery - Chen, Xiaoping; Wang, Tao; Zhang, Yu; Ji, Hongbo; Ji, Yingping; Yuan, Quan; Li, Ling (International journal of energy research, 2020)
Summary The inevitable vehicle collision has made the safety of lithium‐ion battery (LIB) carried by electric vehicles (EVs) a problem that restricts the further and large‐scale promotion of EVs. Therefore, establishing the numerical mechanics model of LIBs and studying their mechanical integrity are imperative. In this study, we design indentation, compression, and drop‐weight experiments for prismatic LIBs (PLIBs). Mechanical integrity and internal short circuit are analyzed in consideration of state of charge (SOC) and dynamic effects. A homogeneous PLIB model that considers anisotropic property, SOC, and dynamic effects is developed for the first time for application in different loading conditions. After its effectiveness is validated, the affecting parameters (ie, SOC and impact velocity) of the mechanical behaviors during dynamic loadings are investigated using the established model. The results show that strain rate effect and SOC state have impact on the mechanical properties of PLIB. However, the strain rate effect has much larger influence than the SOC state. Results may shed lights on the safety design of PLIBs in a mechanical aspect. A homogeneous prismatic lithium‐ion battery (PLIB) model that considers anisotropic property, state of charge (SOC), and dynamic effects is developed. The dynamic behavior of PLIB under high SOC and impact velocity is investigated. The relationship of the mechanical response and short circuit behavior of PLIBs is analyzed.